IBERIAN DOMINANCE AND THE INTRUSION OF THE NORTHERN EUROPEANS INTO THE ATLANTIC WORLD: SLAVE TRADING AS A RESULT OF ECONOMIC GROWTH? - David Eltis (Almanack)
Abstract The British, French and, eventually, the Americans attract a disproportionate share of scholarly attention in the history of the Atlantic World before 1800. The impact of the St. Domingue revolution, British power in the nineteenth century, and the dominance of the American economy in the 20th and 21st centuries have ensured that historians fail to recognize the continued influence of the two Iberian nations in the three centuries after Columbian contact. Until at least 1800 Spanish America was the largest, richest, most heavily populated, as well as the most urbanized European imperial domain in the New World. In the Atlantic Ocean and Africa, the Portuguese had a similar position, not because of conquests, but because of the slave trading system they developed based on their relations with parts of sub-Saharan Africa. They were able to supply slaves to the Americas more efficiently than any other European nation - an advantage that persisted through the whole period of the slave trade.Much of the recent literature - in the US especially - has revived an old argument about how slavery enabled capitalism. But a more accurate picture of the pre-1800 world raises the question of why after three centuries of slavery in the Americas it was northern Europe and North America that first became advanced capitalist societies rather than Iberia and South America. This paper examines the Portuguese system of slave trading and assesses its impact on the transatlantic slave trade and the experiences of the African peoples carried off to the Americas.